The Analysis of Inflationary Shock Results for Polish Economy with the Usage of DSGE Model - Wójcik, Szymon (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
The purpose of study was to analyze a reaction of polish economy for inflationary shock. Study concerned Polish economy from 1998 to 2013. A New Keynesian DSGE model for closed economy was employed. Different levels of autoregression of shocks were also checked. Reaction of variables was illustrated with a usage of impulse response functions (IRF). Results show that as level of autocorrelation of inflationary shock rises, the magnitude and time of returning to steady-state increases.